Construction of a wooden bridge. (Journal of Parents and Teachers, 2013)
This article deals with the topic of assessment of the core competences by means of the project method and the cooperative learning within the area of technology. It offers an instruction sheet and every single step necessary to carry out a wooden bridge as a project for students of the last grade of middle school.
Keywords: Problem-based learning; Competences; Technology; Secondary education; Activities; experience